PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI HOTEL PRINCESS KEISHA BALI & CONVENTION CENTRE - Ni Gusti Ayu Cempaka, Ranti; Sri Sulistyawati, Ni Luh Ketut; I Wayan Jata (Journal of Hotel Management, 2024)
Employees play a crucial role in every organization as they hold the key to success and the ability to accomplish company objectives. Staff performance is an undeniable factor that hotel management must take into account. When staff members perform exceptionally, clients are guaranteed high-quality service. Work discipline is one aspect that influences productivity in the workplace. Employees will become more conscious of the importance of doing a good job on all tasks when there is good work discipline. Finding out how Princess Keisha Bali& Convention Center Hotel's work discipline affects employee performance is the primary goal of this study. The researchers in this quantitative study polled 40 individuals-a representative sample from the entire staff of the Princess Keisha Bali Hotel& Convention Center. This study used saturation sampling techniques for its sampling procedure. Basic linear regression analysis, t-tests, and coefficients of determination are some of the analytical tools used. Work discipline (X) was positively and statistically significantly related to employee performance (, according to the findings. As can be shown in the t-table, the t-value is 10.598=1.684 Employee performance will improve as a result of stricter work rules as work discipline positively affects performance (beta = 1.603). The Princess Keisha Bali &Convention Center Hotel's management hopes to use the findings of this study to encourage more discipline in the workplace and, by extension, higher productivity from its staff.